A Cost-Effectiveness Analysis Of An Adenocarcinoma Risk Prediction Multi-Biomarker Assay For Patients With Barrett’s Esophagus - Hao J; Critchley-Thorne R; Diehl DL; Snyder SR (Dove Medical Press, 2019)
Jing Hao,1 Rebecca Critchley-Thorne,2 David L Diehl,3 Susan R Snyder1 1Department of Epidemiology and Health Services Research, Geisinger, Danville, PA, USA; 2Research & Development, Cernostics Inc, Pittsburgh, PA, USA; 3Department of Gastroenterology, Geisinger, Danville, PA, USACorrespondence: Jing HaoDepartment of Epidemiology and Health Services Research, Geisinger, 100 N Academy Ave, MC44-00, Danville, PA 17822, USATel +1 570 214 2543Fax +1 570 214 9451Email jhao@geisinger.eduPurpose: This study evaluates the cost-effectiveness of a quantitative multi-biomarker assay (the Assay) that stratifies patients with Barrett’s Esophagus (BE) by risk of progression to high-grade dysplasia (HGD) or esophageal adenocarcinoma (EAC) and can be used to guide clinical decisions, versus the current guidelines (standard of care [SOC]) for surveillance and treatment of BE.Patients and methods: Markov decision modeling and simulation were used to compare cost and quality-adjusted life-years (QALYs) from the perspective of a US health insurer with care delivered by an integrated health system. Model assumptions and disease progression probabilities were derived from the literature. Performance metrics for the Assay were from an independent clinical validation study. Cost of the Assay was based on reimbursement rates from multiple payers. Other costs were derived from Geisinger payment data.Results: Base-case model results for a 5-year period comparing the Assay-directed care to the SOC estimated an incremental cost-effectiveness ratio (ICER) of $52,483/QALY in 2012 US dollars. Assay-directed care increased the use of endoscopic treatments by 58.4%, which reduced the progression to HGD, EAC and reduced EAC-related deaths by 51.7%, 47.1%, and 37.6%, respectively, over the 5-year period. Sensitivity analysis indicated that the probability of the Assay being cost-effective compared to the SOC was 57.3% at the $100,000/QALY acceptability threshold.Conclusion: Given the model assumptions, the new Assay would be cost-effective after 5 years and improves patient outcomes due to improvement in the effectiveness of surveillance and treatment protocols resulting in fewer patients progressing to HGD and EAC and fewer EAC-related deaths.Keywords: Barrett’s esophagus, esophageal adenocarcinoma, risk prediction multi-biomarker assay, cost effectiveness